(3OQGSI GdLOhi (B/s - (3UGdM MSf, ZGOIs ((3GdGScfOQjI(B: s (3GdhaGA(B, s, 2008)
(3GdJYQja HOQGSI GdLOhi , OQGSI GdShb ef GdfGMjI GdafjI , GdOQGSI GdJehjdjI , OQGSI GdQHMjI GdJLGQjI , OQGSI GdLOhi GdGbJUGOjI h GdLOhi GdGLJeGYjI , Jbhje LOhi GdeTQhYGJ aj XG YOe GdJGcO , GdJMdjd GdeGdj ddeTQhYGJ GdGSJKeGQjI (B.s
Keywords: (3GdEbJUGOs; (3GdJehjds; (3GdeTGQjY GdESJKeGQjIs